IbM BAGI GURU-GURU BAHASA INGGRIS ALUMNI IKIP PGRI SEMARANG - Dias Andris Susanto; Ratna Kusumawardhani; Entika Fani Prastikawati (Universitas PGRI Semarang, 2013)
IbM BAGI GURU-GURU BAHASA INGGRIS ALUMNI IKIP PGRI SEMARANG